ALAT PENGHITUNG WAKTU PADA PERMAINAN CATUR - Sulistiarawati; Surojo; Ocsirendi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Chess is a popular sport known as a brian teaser game. The word chess it self is an abbreviation of chaturaga which means four corners. Generally, the playing time for a game is 10 – 15 minutes for a fast game, while for a long game the time game can be up to 30 minutes or even an hour. In this final proof, the author creates a chess clock which is used as a tool for calculating time in chess games. This tool was created to create more efficient time when playing chess. The method for making this tool uses Arduino Uno Atemega328 as a control system with input from push-button which is then displayed on the LCD which will be used as a display to set the running time of the game. Then the IM tool is also equipped with a Buzzer as a marker and detector if one of the chess players’ time has ended. In the tool that author created, the time can be set for minutes, around 99 minutes, then for seconds, around 59 seconds.